What we know about the profession of the future - Gedrimė, Lina; Gierasimovič, Zita; Kisielienė, Danguolė; Dadašova, Egita (Slauga. Mokslas ir praktika, 2021)
The function of a nursing assistant is to help the nurse to provide nursing services. The chosen profession requires knowledge, diligence in ensuring the patient's personal hygiene, responsibility in preparing nursing equipment for the procedure. The nurse assistant, as a full-fledged team member, interacts with patients and their loved ones to be tolerant and cultured.
Keywords: nurse's assistant; functions; communication